2006
DOI: 10.1038/sj.jid.5700185
|View full text |Cite
|
Sign up to set email alerts
|

FK506 Controls CD40L-Induced Systemic Autoimmunity in Mice

Abstract: Autoimmunity results from loss of mechanisms controlling self-reactivity. Autoimmune disorders play an increasingly important role and CD40-CD40 ligand (CD40L) interaction on immunocompentent cells is able to break established immunotolerance. To study the effects of the calcineurin-inhibitor FK506 on CD40L-induced systemic autoimmunity, CD40L transgenic (tg) mice, which spontaneously develop a mixed connective tissue-like disease, were treated with FK506 after onset of overt autoimmunity. Interestingly, FK506… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…These data demonstrate that the activation of LC via CD40/CD40L signaling can be the initial event, which triggers a cascade of immune responses resulting in the final breakdown of tolerance against self [12,13]. Besides initiating cutaneous immunity LC can also inhibit cutaneous immune responses and induce tolerance since K14-driven overexpression of RANKL led to immunosuppression, functional alterations of epidermal LC, and a systemic increase of CD4 + CD25 + regulatory T cells [14].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 88%
“…These data demonstrate that the activation of LC via CD40/CD40L signaling can be the initial event, which triggers a cascade of immune responses resulting in the final breakdown of tolerance against self [12,13]. Besides initiating cutaneous immunity LC can also inhibit cutaneous immune responses and induce tolerance since K14-driven overexpression of RANKL led to immunosuppression, functional alterations of epidermal LC, and a systemic increase of CD4 + CD25 + regulatory T cells [14].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 88%
“…For in vivo inhibition of NFAT signaling, FK506 was used to inhibit the activating interaction between calcineurin and NFAT, at a dose of 10 mg/kg (administered i.p. every 3 days) (50). The Stat6 inhibitor, AS1517499, was purchased from Axon Medchem, and was used at a concentration of 50 nM for in vitro use, and dosed at 10 mg/kg for in vivo use (administered i.p.…”
Section: Methodsmentioning
confidence: 99%
“…[130,131] Qian and Dana [132] demonstrated in a BALB c mice model that local ocular administration of anti-CD154 is effective in the prevention of corneal allograft rejection in normal-risk recipients, and in delaying the incidence of rejection in high-risk recipients. Another study [133] showed the beneficial therapeutic effects of tacrolimus for the treatment of CD40L-induced autoimmunity. Taken together, the findings listed above indicate that the anti-inflammatory and antirejection effects of tacrolimus may be partly due to blockade of CD40-CD154 interaction.…”
Section: Reduced Markers Of Apoptosismentioning
confidence: 98%